Cover Picture: Structure of van der Waals bound hybrids of organic semiconductors and transition metal dichalcogenides: the case of acene films on MoS2 (Phys. Status Solidi RRL 12/2016). Issue 12 (December 2016) - Breuer, Tobias; Maßmeyer, Tobias; Mänz, Alexander; Zoerb, Steffen; Harbrecht, Bernd; Witte, Gregor
Abstract : No abstract is available for this article. Abstract : In the field of two‐dimensional materials, transition metal dichalcogenides (TMDCs) are an important representative which have revealed novel physics. Breuer et al. (pp. 905–910 ) used such TMDC surfaces to fabricate crystalline, well‐defined hybrid structures with organic semiconductors. Brought together, the characteristic advantages of both material classes can be combined to fabricate novel synthetic materials with superior characteristics. The authors report on the successful fabrication of such hybrids combining MoS2 with acene‐based molecular donor and acceptor systems. They observe that the materials are structurally compatible and despite strongly different shape symmetries of molecules and substrate, large crystalline molecular islands are formed on high‐quality MoS2 surfaces. Furthermore, they identify the large impact of the structural quality of the TMDC surfaces on the hybrid systems. High surface‐defect densities not only lead to reduced dimensions of the molecular islands. Even the molecular orientation on the surface is inverted, leading to a strongly reduced contact area. Since the preparation of ideal, defect‐free TMDC surfaces is challenging and commercially available TMDCs frequently have considerable defect densities, this aspect requires appropriate consideration for the further advance in this field of material science.